2021
DOI: 10.1111/apa.16163
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of neonatal cerebral perfusion using three‐dimensional power Doppler ultrasound volumes

Abstract: Aim Despite improvement in preterm survival, neurological morbidity remains high. 3D fractional moving blood volume (3D‐FMBV) quantifies neonatal cerebral perfusion by calculating a standardised measure of the amount of moving blood in a region of interest and correlates with tissue perfusion in animal studies. However, its feasibility and reproducibility are yet to be assessed in newborn infants. Methods Fractional moving blood volume analysis was performed on three‐dimensional power Doppler ultrasound (PD‐US… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The study successfully demonstrated the feasibility and reliability of using 3D-FMBV technology to measure cerebral perfusion in a healthy preterm infant population. This technology can perform a correlational analysis with standardized quantification standards by calculating the perfusion of flowing blood in the region of interest, thereby judging the perfusion situation [ 42 ].…”
Section: Evaluation Of Brain Function (Hemodynamics)mentioning
confidence: 99%
“…The study successfully demonstrated the feasibility and reliability of using 3D-FMBV technology to measure cerebral perfusion in a healthy preterm infant population. This technology can perform a correlational analysis with standardized quantification standards by calculating the perfusion of flowing blood in the region of interest, thereby judging the perfusion situation [ 42 ].…”
Section: Evaluation Of Brain Function (Hemodynamics)mentioning
confidence: 99%